Antipsychotic-induced prolactin elevation in premenopausal women with schizophrenia: associations with estrogen, disease severity and cognition - Brand, BA; de Boer, JN; Willemse, EJM; Weickert, CS; Sommer, IE; Weickert, TW (Springer, 2024)
Purpose: Antipsychotic-induced prolactin elevation may impede protective effects of estrogens in women with schizophrenia-spectrum disorders (SSD). Our study sought to confirm whether the use of prolactin-raising antipsychotics is associated with lower estrogen levels, and to investigate how estrogen and prolactin levels relate to symptom severity and cognition in premenopausal women with SSD. Methods: This cross-sectional study included 79 premenopausal women, divided in three groups of women with SSD treated with prolactin-sparing antipsychotics (n = 21) or prolactin-raising antipsychotics (n = 27), and age-matched women without SSD (n = 31). Circulating 17β-estradiol was compared among groups. In patients, we assessed the relationship between prolactin and 17β-estradiol, and the relationships of these hormones to symptom severity and cognition, using correlation analyses and backward regression models. Results: In women receiving prolactin-raising antipsychotics, 17β-estradiol levels were lower as compared to both other groups (H(2) = 8.34; p = 0.015), and prolactin was inversely correlated with 17β-estradiol (r=-0.42, p = 0.030). In the prolactin-raising group, 17β-estradiol correlated positively with verbal fluency (r = 0.52, p = 0.009), and 17β-estradiol and prolactin together explained 29% of the variation in processing speed (β17β−estradiol = 0.24, βprolactin = -0.45, F(2,25) = 5.98, p = 0.008). In the prolactin-sparing group, 17β-estradiol correlated negatively with depression/anxiety (r = -0.57, p = 0.014), and together with prolactin explained 26% of the variation in total symptoms (β17β−estradiol = -0.41, βprolactin = 0.32, F(2,18) = 4.44, p = 0.027). Conclusions: In women with SSD, antipsychotic-induced prolactin elevation was related to lower estrogen levels. Further, estrogens negatively correlated with symptom severity and positively with cognition, whereas prolactin levels correlated negatively with cognition. Our findings stress the clinical importance of maintaining healthy levels of prolactin and estrogens in women with SSD.